Modulação do reinício da meiose de oócitos bovinos pelo fator de crescimento fibroblástico 10, angiotensina II e progesterona em sistema alternativo de cultivo - Gasperin, Bernardo Garziera (2009)
The aim of this study was to evaluate the effect of fibroblast growth factor 10 (FGF10) on bovine oocyte meiotic resumption in an in vitro oocyte and follicular cells co-culture system. At first, an oil-free culture system able to maintain a stable osmolality of the medium without the negative interference of the oil was established. The maintenance of osmotic equilibrium confirms that fourwell plate with water in the central hole can be a feasible alternative to replace oil for scientific experimentation and embryo culture. The embryo development rate in the alternative system (near 30% blastocyst) was similar to that obtained in the conventional system (33% blastocyst). Afterwards, the role of FGF10 on bovine oocyte meiotic resumption was evaluated in a co-culture of oocytes and follicular cells in the presence of angiotensin II (10-11M AngII). All tested concentrations of FGF10 inhibited the resumption of meiosis induced by AngII (P ≤ 0.05). The highest germinal vesicle breakdown (GVBD) rate was observed when FGF10 was absent (45.3%). At concentrations of 10, 100, and 1000ng mL-1 FGF10, the rates of GVBD were 30.2, 29.6 and 27%, respectively. In a second experiment, oocytes were co-cultured with follicular hemisections to test if FGF10 (100ng mL-1) acts directly on COCs or through follicular cells to inhibit AngII (10-11M)-induced meiotic resumption. The AngII-induced GVBD (62.6%) was inhibited when FGF10 was added to in vitro co-culture system (37.8%; P ≤ 0.05). However, FGF10 did not affect meiotic resumption of COCs cultured without AngII in the presence or absence of follicular cells. The third experiment tested if FGF10 inhibits progesterone-induced meiotic resumption. The addition of FGF10 did not affect the meiotic resumption rate induced by progesterone (41.1% and 41.7% GVBD with and without FGF10, respectively; P ≥ 0.05). However, indomethacin (10μM) blocked (20.1% GVBD; P ≤ 0.05) progesterone positive effect suggesting that this steroid, like AngII, acts through cyclooxygenases pathway to induce meiotic resumption. Results show that FGF10 interacts with follicular cells to inhibit AngII but not progesterone-induced meiotic resumption of bovine oocytes.